Pelatihan Pembuatan Ecobrick sebagai Solusi Penanganan Sampah Plastik di SDN Pandean, Kecamatan Pandean, Magelang - Rohana, Evieta; Wulandari, Fitri; Prabhata, Wimzy Rizqy; Ekawati, Nuraini; Anam, Khairul; Rukmi, MG Isworo; Sasikirana, Widyandani (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
The amount of plastic waste is increasing along with its increasing use. Plastic like waste that is not easily decomposed causes problems if it is not handled properly. The school environment is one of the producers of plastic snack packaging waste, including here Pandean Elementary School in Magelang district. One method of recycling plastic waste is to turn it into ecobricks. This method is still not widely applied as a plastic waste recycling method because there is still little information about this method. Therefore, it is necessary to conduct socialization and direct practical examples of making ecobricks that can be formed into other objects that have beneficial values. From the training activities, it can be seen that the Pandean Elementary School students were very enthusiastic because they could practice directly making ecobics and wanted to spread them to the surrounding community.